PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN LECTORA INSPIRE PADA MATA KULIAH SALESMANSHIP - Septyan Adhi Kristanto; Harti; Siti Sri Wulandari; Finisica Dwijayati Patrikha (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2021)
This research has a goal, namely to produce a learning media that can be used to support the lecture process that can be an alternative source of teaching materials for students majoring in commercial administration in studying salesmanship courses, the subject matter of sales promotion, using the Lectora inspire software. The type of research is research and development with a 4D research and development model consisting of the definition stage, the design stage, the development stage, and the dissemination stage. The research subjects are experts consisting of material, media, and language experts as well as users, namely Commerce Education Students. The data collection technique used is a questionnaire or questionnaire used to collect information in testing the feasibility of learning media. Research and development results show that the learning media developed is very valid and feasible to be used in supporting the learning process as well as being an alternative source of student learning